Decreased brain PME/PDE ratio in bipolar disorder: a preliminary 31P magnetic resonance spectroscopy study. (19th October 2015) - Shi, Xian‐Feng; Carlson, Paul J; Sung, Young‐Hoon; Fiedler, Kristen K; Forrest, Lauren N; Hellem, Tracy L; Huber, Rebekah S; Kim, Seong‐Eun; Zuo, Chun; Jeong, Eun‐Kee; Renshaw, Perry F; Kondo, Douglas G
Abstract : Objectives: The aim of the present study was to measure brain phosphorus‐31 magnetic resonance spectroscopy ( 31 P MRS) metabolite levels and the creatine kinase reaction forward rate constant (kf ) in subjects with bipolar disorder (BD). Methods: Subjects with bipolar euthymia (n = 14) or depression (n = 11) were recruited. Healthy comparison subjects (HC) (n = 23) were recruited and matched to subjects with BD on age, gender, and educational level. All studies were performed on a 3‐Tesla clinical magnetic resonance imaging system using a 31 P/ 1 H double‐tuned volume head coil. 31 P spectra were acquired without 1 H‐decoupling using magnetization‐transfer image‐selected in vivo spectroscopy. Metabolite ratios from a brain region that includes the frontal lobe, corpus callosum, thalamus, and occipital lobe are expressed as a percentage of the total phosphorus (TP) signal. Brain pH was also investigated. Results: Beta‐nucleoside‐triphosphate (β‐NTP/TP) in subjects with bipolar depression was positively correlated with kf (p = 0.039, r 2  = 0.39); similar correlations were not observed in bipolar euthymia or HC. In addition, no differences in kf and brain pH were observed among the three diagnostic groups. A decrease in the ratio of phosphomonoesters to phosphodiesters (PME/PDE) was observed in subjects with bipolar depression relative to HC (p = 0.032). We also observed a trend toward an inverse correlation in bipolar depression characterized by decreased phosphocreatine and increased depression severity. Conclusions: In our sample, kf was not altered in the euthymic or depressed mood state in BD. However, decreased PME/PDE in subjects with bipolar depression was consistent with differences in membrane turnover. These data provide preliminary support for alterations in phospholipid metabolism and mitochondrial function in bipolar depression.